Boundary Problem for a Third Order Equation of a Mixed Composite Type - Muminov F.M; Dushatov N.T; Miratoev Z.M. (Genius Journals, 2022)
Investigations of boundary value problems for an equation of composite type are a relatively new direction in the theory of boundary value problems. These problems are of particular interest in connection with their application in various problems of mechanics and physics, such they arise when modeling heat and mass transfer in capillary-porous media of a number of different biological objects and other problems.
Keywords: Nonlocal; nonlocal problem; equations of mixed-composite type; locale